(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
India is the world’s largest milk producer, accounting for 22% of the world’s milk supply in 2017. Five Indian states produced over 50% milk in 2016. The Indian dairy sector also played a major role in raising the socio-economic status of the rural landless, besides small and medium farm households. Besides, this sector helps reduce rural poverty by providing employment opportunities for rural workers, particularly women. Several factors have contributed to India’s rising milk production, including the role of co-operatives. The present study examines the dairy industry’s output and employment performance. Data show that the dairy industry contributes around two percent of the total manufacturing industry output while generating around one percent of the entire manufacturing industry employment jobs. The studies further examine the performance of private, public, and cooperative dairy firms. Data confirm that the Indian co-operative sector contributes about 30% of total revenue, with Indian private companies and government companies/subsidiary companies contributing 23.5% and 11%, respectively. In contrast, foreign firms contribute around 8.6%. Additionally, the study examines the government’s role in India’s milk production while controlling for natural disaster factors. The results show that state government expenditure for dairy development and implementation of dairy-related policies enhanced milk production and per capita availability in the Indian states.